Prove that if $f(0)=0$ and $f'(0)=0$, then $f(x)=0$ for all $x$.

Hint: The idea is to multiply both sides of the equation $f''(x)+ f(x) = 0$ by something that makes the left-hand side of the equation into the derivative of something.

I'm not sure how to proceed and don't really understand the hint.


$$f''(x)+ f(x) = 0 $$

$$ f'(x) f''(x) +f'(x)f(x) =0 $$

$$ (1/2)(f^2 + f'^2 )' =0$$

$$f^2 + f'^2=C$$

Since $$ (f^2 + f'^2)(0)=0$$

We get $C=0$, that is $f(x)=0$

  • $\begingroup$ could you explain the last step, I'm really confused. $\endgroup$ – MANONMARS45 May 12 '18 at 8:11
  • $\begingroup$ we know $f(0)=f'(0)=0$, thus$ f^2(0)+f'^2(0)=0$. That gives us $C=0$ from which we get $f^2+f'^2=0$, so$ f=f'=0$ for all $ x$. $\endgroup$ – Mohammad Riazi-Kermani May 12 '18 at 9:15

Multiply by f'. It becomes $((f^2)'+(f'^2)')/2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.